Tourism under climate crisis in Asia: impacts and implications - Fang, Yan; Trupp, Alexander *; Hess, Janto S.; Ma, Siyao (Taylor and Francis Group, 2022)
Study of the implications of Asian tourism for climate change is critical to fulfilling the terms of the UN Climate Change Conference in Glasgow (COP26) and reaching the Sustainable Development Goals. Research has only recently begun to cover these topics. This paper examines climate risks, adaptation response, carbon emission, and mitigation in Asian tourism by reviewing the state-of-the-art and identifying gaps in previous research and future directions. More work has been done on East, Southeast, and South Asia than on Central, West, and North Asia, but great differences exist among needed research topics in these subregions. While some progress has been made on impact assessments of climate change and carbon emissions estimations, analysis and action remain mismatched. Often, one tourism sector is analyzed in isolation and only general suggestions are given for climate change adaptation and mitigation. This therefore highlights research that can facilitate the integrated analysis of climate change to inform policymakers and the public.